Structure and function of oxidation-reduction enzymes : proceedings of the Wenner-Gren symposium held at the Wenner-Gren Center, Stockholm, 23-27 August, 1970 - Akeson, A; Ehrenberg, A. (Anders) (Wenner-Gren Center international symposium series, 1972)
Structure and Function of Oxidation-Reduction Enzymes is a collection of papers presented at the Wenner-Gren Symposium held at the Wenner-Gren Center, Stockholm on August 23-27, 1970. It provides important understanding of the structure and function of oxidation-reduction enzymes: iron, flavin, and nicotinamide enzymes.